17β‐estradiol reduces Cav1.2 channel abundance and attenuates Ca2+‐dependent contractions in coronary arteries. Issue 5 (11th September 2017) - Hill, Brent J.F.; Dalton, Robin J.; Joseph, Biny K.; Thakali, Keshari M.; Rusch, Nancy J.
Abstract: One mechanism by which the female sex may protect against elevated coronary vascular tone is inhibition of Ca 2+ entry into arterial smooth muscle cells (ASMCs). In vitro findings confirm that high estrogen concentrations directly inhibit voltage‐dependent Cav 1.2 channels in coronary ASMCs. For this study, we hypothesized that the nonacute, in vitro exposure of coronary arteries to a low concentration of 17 β ‐estradiol (17 β E) reduces the expression of Cav 1.2 channel proteins in coronary ASMCs. Segments of the right coronary artery obtained from sexually mature female pigs were mounted for isometric tension recording. As expected, our results indicate that high concentrations (≥10 μ mol/L) of 17 β E acutely attenuated Ca 2+ ‐dependent contractions to depolarizing KCl stimuli. Interestingly, culturing coronary arteries for 24 h in a 10, 000‐fold lower concentration (1 nmol/L) of 17 β E also attenuated KCl‐induced contractions and reduced the contractile response to the Cav 1.2 agonist, FPL64176, by 50%. Western blots revealed that 1 nmol/L 17 β E decreased protein expression of the pore‐forming α 1C subunit (Cav α ) of the Cav 1.2 channel by 35%; this response did not depend on an intact endothelium. The 17 β E‐induced loss of Cav α protein in coronary arteries was prevented by the estrogen ER α /ER β antagonist, ICI 182, 780, whereas the GPER antagonist, G15, did not prevent it. There was no effect of 1 nmol/L 17 β E on Cav α transcript expression. We conclude that 17 β E reduces Cav 1.2 channel abundance in isolated coronary arteries by a posttranscriptional process. This unrecognized effect of estrogen may confer physiological protection against the development of abnormal Ca 2+ ‐dependent coronary vascular tone.